GRID TIE INVERTER UNTUK PLTS ATAP DI INDONESIA: REVIEW STANDAR DAN INVERTER YANG COMPLIANCE DI PASAR DOMESTIK - P.G.G. Priajana; I.N.S. Kumara; I.N. Setiawan (Program Studi Teknik Elektro UNUD, 2020)
The Government started a million solar rooftop movement to help accelerate Indonesia'srenewable energy target in 2025. In effect of ministerial regulation 49/2018, householdcustomers are able to install grid tie photovoltaic and export excess energy to PLN. Inverter is acomplex and a vital component to the performance of grid tie photovoltaic systems, thereforeinverter used must follow applicable standard. This article reviews the avaibility of inverters forsolar rooftop in Indonesia. The purpose of this article is to know the avaibility of inverter andhow they are seen from applicable standard. From this research produced inverter databaseconsisted of 513 inverter models. Inverter database then analyzed seen from its manufacturingstatus, inverter power output capacity, THD output, efficiency, and price. This information iscrucial in choosing quality inverter so rooftop photovoltaic would work effectively andsustainably. Presently various inverters with capacity 0,5 kW - 10 kW already available which issuitable for solar rooftop application. There are already plenty inverters with THD output <3%that conform with Indonesia’s standard but many also still have not listed their THD output.Inverter efficiency is already >95% and available with an average price of Rp3,435,380/kW. Listof inverter models that conform standard and certification presented in a table which served asoutput of this research.